2018
DOI: 10.15419/bmrat.v5i7.455
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phototherapy on pro-oxidant/antioxidant balance in newborns with Jaundice

Abstract: Introduction: Jaundice is the most common condition requiring medical attention in newborns. Phototherapy is the standard treatment for jaundice. However, in recent decades, phototherapy has been considered as an oxidative stress that can cause lipid peroxidation and damage to DNA. Accordingly, the present study was conducted to examine the possible effects of phototherapy on the Pro-oxidant/Antioxidant Balance (PAB) in jaundiced newborns. Methods: The present clinical trial was conducted on 70 icteric t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…Furthermore, another study by the same author suggested that phototherapy can cause peroxidation of lipids and damage to DNA (11). In confirmation of the previous study, another research demonstrated that as an infant's bilirubin level decreases with phototherapy the balance of oxidant-antioxidant is disrupted toward antioxidant depletion (9). Results of the other investigation likewise showed that blood exchange causes an oxidantantioxidant imbalance in favor of the oxidants (12).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Furthermore, another study by the same author suggested that phototherapy can cause peroxidation of lipids and damage to DNA (11). In confirmation of the previous study, another research demonstrated that as an infant's bilirubin level decreases with phototherapy the balance of oxidant-antioxidant is disrupted toward antioxidant depletion (9). Results of the other investigation likewise showed that blood exchange causes an oxidantantioxidant imbalance in favor of the oxidants (12).…”
Section: Discussionmentioning
confidence: 55%
“…On the other hand, treatment of physiologic jaundice is not risk-free, therefore overtreatment must be done with caution (9). The most common and effective treatment for jaundice is phototherapy which is known to be a safe and tolerable method in infants (10).…”
Section: Introductionmentioning
confidence: 99%
“…The findings of a study comparing PAB levels in neonates with and without asphyxia indicated mean PAB levels were 20 and 40 HK in healthy neonates and neonates with asphyxia, respectively ( 5 ). In two other studies, the mean PAB of neonates was reported to be about 40 HK after jaundice recovery ( 25 , 26 ). A study investigated the effects of selenium consumption, critical to the function of some anti-oxidant enzymes, during pregnancy on the PAB levels of neonates.…”
Section: Discussionmentioning
confidence: 90%
“…Em relação ao estresse oxidativo, os estudos trazem evidências que afirmam que tanto a fototerapia convencional quanto a fototerapia de LED aumentam o índice de estresse oxidativo (OSI), assim como do estresse oxidativo total (TOS) tanto em recém-nascidos ictéricos a termo e prematuros quanto em recém-nascidos com hiperbilirrubinemia hemolítica (Mokhtar, et al, 2019), também corroborando para que a capacidade antioxidante total (TAC) diminuísse a nível sérico em todos os estudos, com maior significância nos recém-nascidos sob fototerapia convencional (Kale, et al, 2013;Boskabadi, et al;2018;Mokhtar, et al, 2019). Foi achada relação significativa entre o TOS sérico aumentado e a fototerapia convencional com luzes fluorescentes azuis e a fototerapia intensiva por LED, porém a fototerapia por LED com almofada de fibra óptica não possuiu significância no aumento do TOS (Kale, et al, 2013).…”
Section: Resultsunclassified